AIR GAP CONTROL SYSTEM FOR HYDROGENERATORS - I. O. Zaitsev; A. S. Levytskyi; V. E. Sydorchuk (Приборы и методы измерений, 2017)
In this paper, we report of the solving the actual problem of control the air gap in the hydrogenerators. The aim of the study was development of a computerized information-measuring system for measuring the air gap in the hydrogenator, which used two capacitive sensors with parallel coplanar electrodes, and the method of determining the shape of the envelope parameters hydrogenerator rotor poles relative to the center axis of rotation, using the measurement results of the air gap.In practical studies of the sensor circuit it has been shown that its use allows for the informative value of the sensor capacitance conversion function to obtain a high accuracy and resolution measurement with digital linearization of converting function of the sensor with use program utility. To determine the form deviations of the envelope line of the rotor pole from the ideal cylinder, which is one of the main structural defects of the technological errors as results the distortion of the shape of the air gap in the hydrogenator, when the machine was manufacture and assembly. It is proposed to describe the shape of the envelope to use a Fourier transform. Calculation of the coefficients of the Fourier series is performed using the method of least squares as the regression coefficients.Application of this method in processing the measuring data in a computerized information-measuring system the developed with the primary converter with coplanar parallel electrodes allowed attaining the high measurement accuracy and resolution informative in magnitude of the capacity.